The Wonders of Diptera Characteristics, Diversity, and Significance for the World's Ecosystems - Khan Perveen, Farzana (IntechOpen, 2021)
This book provides comprehensive and concise knowledge about Diptera, an order of insects that has both useful and harmful aspects for humans, animals, plants, and the environment. Insects of this order act as agricultural pests as well as vectors of diseases and carriers of microorganisms. Chapters cover such topics as characteristics of different types of Dipteran insects including fruit flies, mosquitos, and midges, and strategies to control insect populations to combat the spread of human and animal diseases such as dengue, trypanosomosis, and others.